Reproductive Cycle of Hard Clam, Meretrix lyrata Sowerby, 1851 (Bivalvia: Veneridae) from Sarawak, Malaysia - Hadi Hamli; Mohd Hanafi Idris; Amy Halimah Rajaee; Abu Hena Mustafa Kamal (Tropical Life Sciences Research, 2015)
A study of the reproductive cycle of the hard clam, Meretrix lyrata, was documented based on histological observation and Gonad Index (GI). Samples were taken from estuarine waters of the Buntal River in Sarawak, Malaysia. The gonad of M. lyrata started to develop in September 2013. Gametogenesis continued to develop until the maturation and spawning stage from February to April 2014. The GI pattern for a one-year cycle showed a significant correlation with chlorophyll a. The corresponding GI with chlorophyll a suggested that the development of the reproductive cycle of M. lyrata required a high amount of food to increase gametogenesis. Kajian ke atas kitaran pembiakan kerang keras Meretrix lyrata adalah berdasarkan kaedah histologi dan Indeks Gonad (GI). Sampel telah dikumpulkan dari muara Sungai Buntal di Kuching, Sarawak, Malaysia Gonad M. lyrata telah bermula berkembang semasa September 2013. Gametogenesis terus berkembang sehingga semua individu mencapai peringkat kematangan dan bertelur pada Februari hingga April 2014. Corak GI untuk kitaran setahun telah menunjukkan hubungan yang ketara dengan klorofil a. GI yang sepadan dengan klorofil a telah mencadangkan bahawa perkembangan kitaran pembiakan M. lyrata memerlukan jumlah makanan yang tinggi untuk meningkatkan gametogenesis.